2014
DOI: 10.1182/blood-2014-05-578963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of induction regimen and stem cell transplantation on outcomes in double-hit lymphoma: a multicenter retrospective analysis

Abstract: Key Points A subset of DHL patients may be cured, and some patients may benefit from intensive induction. Further investigations into the roles of SCT and novel agents are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
388
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(419 citation statements)
references
References 33 publications
15
388
0
16
Order By: Relevance
“…Although early studies of patients with DLBCL bearing MYC and/or BCL2 rearrangements indicated markedly increased risk of CNS involvement at diagnosis of up to 44%, 50,51 2 larger retrospective studies indicated that 4% to 7% of patients had CNS involvement at diagnosis with a 3-year cumulative CNS risk of 13%. 26,52 Both studies also suggested use of CNS prophylaxis may improve outcomes: in the first, IT MTX prophylaxis was associated with a reduction in CNS progression (3-year incidence, 5% v 15%; P 5 .017) 26 ; in the second, use of CNS prophylaxis was associated with improvement in overall survival. 52 We therefore consider HGBL-DH at high risk of CNS involvement and consider these patients for CNS-directed prophylaxis.…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…Although early studies of patients with DLBCL bearing MYC and/or BCL2 rearrangements indicated markedly increased risk of CNS involvement at diagnosis of up to 44%, 50,51 2 larger retrospective studies indicated that 4% to 7% of patients had CNS involvement at diagnosis with a 3-year cumulative CNS risk of 13%. 26,52 Both studies also suggested use of CNS prophylaxis may improve outcomes: in the first, IT MTX prophylaxis was associated with a reduction in CNS progression (3-year incidence, 5% v 15%; P 5 .017) 26 ; in the second, use of CNS prophylaxis was associated with improvement in overall survival. 52 We therefore consider HGBL-DH at high risk of CNS involvement and consider these patients for CNS-directed prophylaxis.…”
Section: Casementioning
confidence: 99%
“…26,52 Both studies also suggested use of CNS prophylaxis may improve outcomes: in the first, IT MTX prophylaxis was associated with a reduction in CNS progression (3-year incidence, 5% v 15%; P 5 .017) 26 ; in the second, use of CNS prophylaxis was associated with improvement in overall survival. 52 We therefore consider HGBL-DH at high risk of CNS involvement and consider these patients for CNS-directed prophylaxis. The 2017 WHO categories of HGBL-DH and HGBL not otherwise specified (HGBL-NOS) have created difficulty in applying evidence from older datasets (based on the superseded BCL-U).…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…5 In a recent multi-center trial involving patients with double-hit lymphomas treated with high-intensity chemotherapy regimens, the progressionfree survival and overall survival rates at 2 years were 40% and 49%, respectively. 5 An alternate regimen that has been recently shown to be effective for penetration into the cerebrospinal fluid consists of rituximab, cyclophosphamide, vincristine, doxorubicin, and dexamethasone (R-hyperCVAD). 6 This regimen, however, is more cumbersome and has the potential to cause severe toxicity.…”
Section: To the Editormentioning
confidence: 99%
“…Patients with DHL can frequently present with adverse prognostic findings such as advanced clinical stage, elevated lactate dehydrogenase level and increased Ki67 expression on immunohistochemical staining [1,2]; however, baseline clinicopathologic characteristics may not be predictive of the presence of double hit lymphoma in patients diagnosed with aggressive B cell NHL [3].…”
mentioning
confidence: 99%